Systematic literature review and bibliometric analysis of archivist competencies in digital curation - Aviazka Firdhaussi Azmir; Tamara Adriani Salim (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. Digital curation tasks and objectives align with the task of archivists who must digitally plan to ensure safe long-term preservation. As information professionals, archivists must master competencies to become digital curators in the future. This study aims to determine what competencies an archivist must have in digital curation. Data Collection Methods. This study uses a systematic literature review (SLR) available in SCOPUS from 2018-2022, considering 11 selected articles. This study also applied bibliometric analysis using VOSViewer to identify the main characteristics, discuss, and provide research opportunities in this field. Data Analysis. In the first phase, SLR consists of three steps: planning, conducting, and reporting. In the second phase, the bibliometric using co-occurrence analysis to visualize the keyword network, density, and overlay visualization. Results and Discussion. The results of the bibliometric analysis indicate that there are still several topics regarding digital curation that have not been widely studied, including those related to competence, cultural heritages, data management, career, and learning. Based on the systematic literature review there are 11 selected articles that are relevant to research topics and used for data analysis. Conclusion. From 11 selected articles, it was found that archivist competencies in digital curation can be divided into four categories: cognitive, functional, social, and meta competence. The competencies found have implications for archivists as future digital curators by combining technical skills, including expertise in metadata standards and information organization, as well as personal skills. Based on the findings, it also can be an opportunity for further research to examine digital curation competency seen in the topics that are still rarely studied.